Smart Parking IoT Based: Design and Prototype - Amalia, Direstu; Hadiansyah, Rangga; Septiani, Virma (JMKSP (Jurnal Manajemen, Kepemimpinan, dan Supervisi Pendidikan), 2022)
The Arduino Mega 2560 microcontroller is utilized as the processor in this study to construct an IoT-based smart parking prototype. By using research and development methods, system and infrastructure prototypes using sensors, processors, and web-based reservation apps are now the techniques used. Users may select parking slots and view slots available using HMI and an online reservation application designed using App Inventor. This display communicates with the system in real time over the internet. The hardware is environmentally beneficial because it is energy efficient and long-lasting. The smart parking system design has been extensively tested in the past. However, in this study, the payment system is examined, where payments will only be calculated when the user enters and exits the designated parking slot. Through this design, it is hoped that there will be product contributions that can be implemented into society and become a new practical model for learning microcontrollers.